If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 17x + -8 + 2 = -9x + 2 + -8 Reorder the terms: -8 + 2 + 10x + 17x = -9x + 2 + -8 Combine like terms: -8 + 2 = -6 -6 + 10x + 17x = -9x + 2 + -8 Combine like terms: 10x + 17x = 27x -6 + 27x = -9x + 2 + -8 Reorder the terms: -6 + 27x = 2 + -8 + -9x Combine like terms: 2 + -8 = -6 -6 + 27x = -6 + -9x Add '6' to each side of the equation. -6 + 6 + 27x = -6 + 6 + -9x Combine like terms: -6 + 6 = 0 0 + 27x = -6 + 6 + -9x 27x = -6 + 6 + -9x Combine like terms: -6 + 6 = 0 27x = 0 + -9x 27x = -9x Solving 27x = -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 27x + 9x = -9x + 9x Combine like terms: 27x + 9x = 36x 36x = -9x + 9x Combine like terms: -9x + 9x = 0 36x = 0 Divide each side by '36'. x = 0 Simplifying x = 0
| 5(3x-5)-3=5(x-5)+8 | | log(-3x^2+3x-5)=0 | | 2x+9y=145 | | 4-4x-x^2+x^3=0 | | 3x+6+x+5=90 | | logx=-1.5 | | x^4-14x^2=32 | | p^2+14=9p | | 6+55x=33x+10 | | -10x+5(0)=-50 | | 2x^3=100x^2 | | -60a^2b^2-7ab=-1 | | 0.3*c+4=19 | | 6+55x=333 | | -10(0)+5y=-50 | | log^4(8x)=6 | | 2x^3+50x^2=0 | | 7(3d-8)= | | 17x^2+16x+4= | | 2(n+5)=4n+10 | | h^3+1=0 | | 2(5x+1)=10x-3 | | m-14=37 | | 1.9q-4.1-4.2q=3.3q-5.1 | | 8-4(x-2)=8 | | 9(x-7)=-18.9 | | 2x+6y=145 | | 4(a+5)=44.8 | | 5(0)-4y=-20 | | 3=5c-8 | | 40+4x-16=13x-12-3x | | 9e-3=79.8 |